2009
DOI: 10.1107/s1600536809035648
|View full text |Cite
|
Sign up to set email alerts
|

3,6,9,16,19,22-Hexaazatricyclo[22.2.2.211,14]triaconta-1(27),11 (30),12,14(29),24(28),25-hexaene hexakis(p-toluenesulfonate) dihydrate

Abstract: In the title compound, C24H44N6 6+·6C7H7O3S−·2H2O, the macrocycle crystallizes in its hexa­protonated form, accompanied by six p-toluene­sulfonate ions and two water mol­ecules, and lies on an inversion center. The three independent p-toluene­sulfonate anions and their inversion equivalents at (1 − x, 1 − y, 1 − z) are linked to the macrocyclic cation through N—H⋯O hydrogen bonds. Of these, two p-toluene­sulfonate ions are located on opposite sides of the macrocyclic plane and are linked to bridgehead N atoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…A similar binding was also reported by Spiccia for [18]N 6 11a and by Steed for metacyclophanes11b complexing chloride, bromide, or iodide. On the other hand, a p -xylyl-based macrocycle with a slightly larger cavity was reported to form ditopic complexes in a “cross binding” with 3,5-dinitrobenzoate,12 “bipyramidal binding” with tosylate13 and “face binding” with perchlorate 14. However, to the best of our knowledge, complete encapsulation of two anions (fashion d ) in an azamacrocycle-based ligand has not been reported before, although such binding is present in neutral ligands coordinating two transition metal ions 5,15.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A similar binding was also reported by Spiccia for [18]N 6 11a and by Steed for metacyclophanes11b complexing chloride, bromide, or iodide. On the other hand, a p -xylyl-based macrocycle with a slightly larger cavity was reported to form ditopic complexes in a “cross binding” with 3,5-dinitrobenzoate,12 “bipyramidal binding” with tosylate13 and “face binding” with perchlorate 14. However, to the best of our knowledge, complete encapsulation of two anions (fashion d ) in an azamacrocycle-based ligand has not been reported before, although such binding is present in neutral ligands coordinating two transition metal ions 5,15.…”
mentioning
confidence: 99%
“…Ab initio calculations performed on the ligand-chloride complex not only support the stabilization of two chlorides inside the highly charged cavity, but also suggest that the complex with two encapsulated chlorides is energetically more favorable than that with one chloride. While there are many examples of ditopic binding of anions in different fashions (Chart 1a-c), 6,7,[11][12][13][14] the complete encapsulation of two anionic guests has not been previously shown in an azamacrocycle-based ligand. The presence of two methyl groups coupled with fully charged nitrogens makes the ligand ideal for fitting two compatible chlorides inside the cavity through trigonal recognition with three hydrogen bonds.…”
mentioning
confidence: 99%
“…The structure of free H 2 L 2+ was optimized in a rectangular fashion (Fig. 4A) as seen in the p -xylyl macrocycle13 and forms a suitable cavity to host an anion. From our DFT-optimized complexes, we found that the ligand deformed its geometry in order to encapsulate each of the anions.…”
mentioning
confidence: 99%
“…The above binding constants are not strong, as expected in water - a competitive polar solvent. The anionic guest also competes with surrounding tosylates that are likely associated with macrocyclic cations 21. Attempts to study in non-polar solvent like CDCl 3 or CD 3 CN were hampered due to the poor solubility of the ligand salts.…”
mentioning
confidence: 99%